Objectivity in dressage judging: New horizons that arise from learning theory - Mclean, A. (DCA Report; Nr. 044, 2014)
`Shaping` is the scalar approximation of a precise response. It is widely accepted as an essential component in the translation of learning processes to training principles in trained species. In the equestrian dressage domain, it is important that judges are able to distinguish training successes and errors in a systematic and scalar way. It follows that if training is a result of a scalar shaping (ISES principle no. 3), then the analysis or judgement of training should be de-constructed with the same shaping scale. Despite recent attempts by the FEI to improve judging, this ambition is inhibited by traditional, subjective terminology and also by a judging scale, known as the German Training Scale, that is not scalar and which comprises a mixture of both subjective and objective elements. Outside the equestrian sphere, in sports where subjectivity also has the potential to pollute objective judging, for example gymnastics and diving, a judging revolution has occurred in order to objectify performances and justify results. Although dressage may be seen as more complicated than say, gymnastics, it is argued here that the difference arises more from the subjectivity and ambiguities that still haunt dressage coaching, training and judging. In this presentation, I propose to dissect the German Training Scale from the various viewpoints of a scientific appraisal of shaping, from identifying subjective as opposed to objective elements of that scale and in highlighting subjective, ambiguous and scientifically flawed terminology that interfere with the judging process. In the final part of the presentation, I introduce an alternative judging scale that arises from a more empirical approach to an analysis of trained responses and that can also be employed in basic form in all equestrian sports where judging involves an analysis of dimensional (wide-ranging) as well as categorical (discrete) qualities. This scale is peer-reviewed and evidenced-based, and comprises elements that are directly observable in all training endeavours. As a training scale it informs the training of a horse to walk a circle, lengthen the trot, perform a half-pass, pirouette or piaffe. It can also be used to load a horse in a trailer or other in-hand manoevres. In fact, every conceivable trained response in any species can be most efficiently achieved using this scale. LP: Introduction of a new, objective training scale heralds a significant judging revolution in dressage and other horse sports. It will not only allow judging to become more accurate, fair and easy, but will also improve the welfare of the equine participants. This will ultimately contribute to the longevity of equestrian sports which is currently threatened in part by the lack of objective precision of contemporary judging guidelines at all levels.